Polyostotic fibrous dysplasia with epiphyseal involvement of the proximal femur in a child: a case report and review of the literature - Elio Paris; Giacomo De Marco; Oscar Vazquez; Sana Boudabbous; Christina Steiger; Romain Dayer; Dimitri Ceroni (Frontiers in Pediatrics)
Fibrous dysplasia (FD) is a benign medullary fibro-osseous anomaly that compromises the mechanical strength of bones, especially the long bones that bear strong mechanical stresses. It can lead to an inability to remodel immature bone into mature lamellar bone, resulting in inappropriate bone alignment in response to mechanical stresses. This case study describes a rare case of polyostotic FD presenting with an epiphyseal lesion of the proximal femoral head in its weight-bearing zone, accompanied by an unconventional femoral malrotation. The present case leads us to recommend that clinicians should not underestimate the occurrence of other deformities, such as the retrotorsion or flexion deformities that can compromise bone structure and the hip's biomechanics. Finally, the involvement of the epiphysis is probably more common than usually thought, introducing an additional complexity since juxta-articular lesions in weight-bearing joints may collapse, compromising articular congruence and function. To minimise this risk, bone scintigraphy and MRI should play a critical role in the patient's workup, evaluation, prognosis and follow-up.